ANALISIS AKUNTANSI PERTANGGUNGJAWABAN PUSAT LABA GUNA ALAT PENILAIAN KINERJA MANAJER PT. PASIFIC MEDAN INDUSTRI - Mekar Meilisa Amalia; Emma Syahfira (Worksheet : Jurnal Akuntansi, 2022)
Responsibility accounting requires each manager to be involved financially for his part, and to present performance reports in a timely manner by comparing actual results with planned. The purpose of this research is to identify and analyze the use of responsibility accounting in assessing the performance of profit center managers and to identify and analyze the factors causing the company's profit targets not to be achieved. This type of research is descriptive quantitative and the source of data used in this study is primary data in the form of financial statements and company accounting records, while secondary data in the form of company profiles.Data collection methods used in this research are interviews, literature study, and documentation. The data analysis technique used is a qualitative descriptive technique. The results showed that the use of profit center responsibility accounting in assessing the performance of managers at PT. Pacific Medan Industry is still not implemented optimally. It is known that there has been a large difference in losses between the realization and the budget from 2016 to 2020, which ranges from 2.04% to 25.14%. The financial manager is less careful in predicting the net profit so there is still a fairly large difference in losses. Factors causing not achieving the company's profit target include the existence of expenses that exceed the previously budgeted amount, including due to price increases.